Math

Which equation is equivalent to
3(2x + 7) = 27

A. (3 * 2x) + 7 = 27

B. (3 * 9) x = 27

C. (3 * 2) + 3 * (x + 7) = 27

D. (3 * 2x) + (3 * 7) = 27
my answer is D. is it right

1. 👍 0
2. 👎 0
3. 👁 52
1. Yes, D.

1. 👍 0
2. 👎 0

Similar Questions

1. math 116

find an equivalent equation with the given denominator 7/b= ?/b squared the expression that is equivalent to 7/b is ? if b is squared wouldn't the 7 also have to be squared to be equivalent? 7/b = 49/b squared? Am I correct?

asked by Amie on November 20, 2009
2. Math

1. 0.24% as a decimal? Is it 0.0024? 2. 135% as a decimal? Is it 1.35? 3. 1/5% as a decimal? Is it 0.2? 4. fraction equivalent to 0.75% is... Is it 3/4? 5. mixed number equivalent to 420% is... Is it 4 1/5? 6. percent equivalent

asked by China on January 13, 2016
3. Calculus

How do I rewrite log4 1=0 as an equivalent exponential equation? How do I rewrite 4 to the -2 power = 1/16 as an equivalent logarithmic equation? Any help is greatly appreciated. If 4 is the BASE of the logarithm, then log (1) = 0

asked by Abby M. on January 13, 2007
4. Math (and note to DAMON)

1. 0.24% as a decimal? Is it 0.0024? 2. 135% as a decimal? Is it 1.35? 3. 1/5% as a decimal? Is it 0.2? 4. fraction equivalent to 0.75% is... Is it 3/4? 5. mixed number equivalent to 420% is... Is it 4 1/5? 6. percent equivalent

asked by China on January 13, 2016
5. math

can someone correct these for me. 8x –4y = 16 y = 2x –4 My answer: This problem does not have a unique solution. This problem therefore is consistent and dependent These equations are the same. If you solve the first one for

asked by jasmine20 on December 23, 2006
6. algebra 2

If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to x from the first equation is substituted into the second equation. x + y = 2 3x + 2y = 9

asked by mel on August 16, 2012
7. Algebra 2

If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to x from the first equation is substituted into the second equation. x – 2y = 2 x + 3y = 17

asked by Mike on April 25, 2011
8. Alegebra 1

Each pair of equations below is equivalent. What was done to the first to get the second; in other words something was done to both sides of the first equation to "turn it into" the second equation - what was done to the first

asked by Gamzee :o) on August 20, 2012
9. math

4. From your equation, find the European equivalent for U. S. size 8. equation~ m = (y2 – y1) / (x2 – x1) m = (39-34) / (5-3) m = 5/2 b=26.5 Equation = y=5/2x+26.5 Can someone please help me answer this? I have a graph if you

asked by Abby on November 3, 2015
10. MATH!!!! AHHH!!!

Im studying for finals! A system of equations is shown below: 8x + 5y = 9 3x + 2y = 4 Part A: Create an equivalent system of equations by replacing one equation with the sum of that equation and a multiple of the other. Show the

asked by Bella on January 14, 2015
11. algebra

Rewrite the following as an equivalent logarithmic equation.Do not solve. y^t = x answer logy+logt=logx-is this right also Express as an equivalent expression that is a sum of logt (3ab) the t is at the bottom of the g answer

asked by dani on May 5, 2010

More Similar Questions